Survey and analysis on the resource situation of primary health care institutions in rural China - Zhang, Zhaoting (Frontiers in Public Health, 2024)
China's rural population is immense, and to ensure the well-being of rural residents through healthcare services, it is essential to analyze the resources of rural grassroots healthcare institutions in China. The objective of this study is to examine the discrepancies in resources between rural grassroots healthcare institutions and the national average in China, to enhance rural healthcare. The methodology entailed the examination of data spanning from 2020 to 2022 about the number of healthcare establishments, the capacity of hospital beds, the number of healthcare professionals, and the count of physicians in both rural and national settings. The findings unveiled substantial disparities. Rural areas had an average of 2.2 fewer healthcare institutions per 10,000 persons compared to the national rate over a span of three years. The number of beds in healthcare institutions in rural areas was around 36 beds lower per 10,000 persons. Rural areas saw a shortage of workers, with around 48 fewer healthcare technical personnel and 10 fewer practicing (including assistant) physicians per 10,000 persons compared to the national average. The study finds that there are significant discrepancies and deficiencies in rural grassroots healthcare resources in China when compared to the national average. This underscores the necessity for enhanced funding to progressively enhance the number of healthcare institutions in rural areas, expand the number of workers, and elevate medical standards to better correspond with national benchmarks. Improving rural healthcare resources will strategically equip these institutions to cater to rural communities and effectively handle public health emergencies. It is crucial to ensure that the rural population in China has equal access to healthcare services as the rest of the country to promote their well-being and achieve health equity.